Cellulose ether with delayed solubility and reduced glyoxal content
Patent Information
- Application Number
- KR1020227039318
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-04-09
- Filing Date
- 2021-04-08
- Publication Date
- 2026-09-04
- Estimated Expiration
- 2041-04-08
Smart Images

Figure 112022119302824-PCT00001 
Figure 112022119302824-PCT00002 
Figure 112022119302824-PCT00003
Abstract
Description
Technology Field
[0001] The present invention relates to a method for producing a cellulose derivative having delayed water solubility by reversibly crosslinking with glyoxal. Background Technology
[0002] Cellulose ethers are used for various purposes, such as thickeners, adhesives, binders and dispersants, wetting agents, protective colloids and stabilizers, and also suspending agents, emulsifiers, and film-forming agents, due to their excellent properties, such as swelling, gel formation, and dissolution behavior.
[0003] These applications require that cellulose ethers be emulsified, dispersed, or dissolved without lumps. However, dissolving cellulose ethers in water in dry powder form often results in surface gelation and lump formation. This problem can be resolved by treating with sufficient amounts of dialdehyde, particularly glyoxal. Through the formation of hemiacetals influenced by acidic catalytic mechanisms, reversible crosslinking is generated that improves dispersibility, delays dissolution in water, and prevents lump formation without substantially affecting solubility. This delayed dissolution can be reduced by increasing the pH ("Cellulose Ethers", Chapter 2.1, Ullmann's Encyclopedia of Industrial Chemistry, 2006, Wiley-VCH Verlag GmbH, Weinheim, Germany).
[0004] WO 2017 / 064164 A1 discloses a cellulose ether temporarily crosslinked with a glyoxalic acid (C1-C4)alkyl ester mono(C1-C4)alkyl acetal. The fraction of the crosslinking agent is preferably 0.01 to 10 parts by weight per 100 parts by weight of the cellulose ether. EP 2 177 538 A1 relates to a cellulose ether containing alkyl and hydroxyethyl groups, which is mixed with a crosslinking agent and then subjected to a grinding-drying process. The crosslinking agent is preferably a monoaldehyde or a dialdehyde, more preferably glyoxal. According to US 2019 / 0062458 A1, the crosslinked water-insoluble cellulose is used to produce membranes or hydrogels. The crosslinking agent may be an aldehyde, organochloride, ether, polyfunctional carboxylic acid, glycerol, urea derivative, and / or glycidyl ether.
[0005] DE 10 75 773 discloses the crosslinking of cellulose ether and glyoxal for improved solubility and / or to prevent aggregation during dissolution. For said crosslinking, cellulose ether was suspended in acetone and an aqueous solution of glyoxal was added.
[0006] US 3072635 discloses a method for producing a water-dispersible cellulose derivative by treating a cellulose ether with 0.001 to 0.2 mol of glyoxal per mol of anhydrous glucose unit, wherein the glyoxal is soluble in alcohol and the cellulose ether preferably contains 1.25 to 5.0 wt% of glyoxal.
[0007] Part of the disclosure in DE 12 39 672 is the possibility of controlling the degree of crosslinking and, consequently, delayed dissolution through the amount of glyoxal. This becomes evident from the given examples. Here, water-soluble methylcellulose is homogeneously kneaded with glyoxal at a concentration of 0.001 to 0.2 mol per mol of anhydrous glucose units of methylcellulose in a pH range of 2 to 7, dried, and ground. At pH 2 (set using phosphoric acid), 0.48 wt% of glyoxal in the cellulose derivative was found to result in a solvation delay of 15 minutes. No figures were provided for the unbound glyoxal content. Furthermore, there was no description of crosslinking at higher pH values, nor any explanation of the associated solvation delay.
[0008] EP 0 597 364 discloses a method of adding sodium dihydrogen phosphate to a glyoxal solution.
[0009] EP 1 316 563 A1 relates to a method for preparing glyoxal-crosslinked cellulose ethers without the addition of an acidic catalyst. In this case, the decrease in viscosity is reduced as the pH of the cellulose ether increases. It should be noted that the solvation retardation is reduced as a result of the increase in pH. The retardation time in deionized water of a methylhydroxyethylcellulose MHEC containing 1.7 wt% glyoxal and a pH of 6.2 is only 20 minutes, compared to the retardation time of 60 minutes for a crosslinked MHEC containing 2.0 wt% glyoxal and a pH of 4.7.
[0010] Glyoxal is classified as irritant and also sensitizing under the CLP Regulation (Regulation (EC) No. 1272 / 2008) and is presumed to have mutagenic effects on humans. Products with a free glyoxal content of 0.1 to 1% must be labeled in compliance with the CLP Regulation. Glyoxal-crosslinked cellulose ethers may be used in the personal care sector provided that the cosmetic producer guarantees that the final product does not exceed the permissible glyoxal concentration of 100 ppm (SCCP / 0881 / 05). Since glyoxal used for reversible crosslinking is re-released when the cellulose ether dissolves in an aqueous medium, it is necessary to minimize the total amount of glyoxal in the final product according to the classification of the CLP Regulation, as well as ensure that it is not bound.
[0011] EP 1 452 544 B1 discloses a method for preparing cellulose ethers having a reduced unbound glyoxal content by adding a water-soluble borate or aluminum salt to a phosphate-buffered crosslinking agent solution. In the aforementioned literature, it is also evident that while the amount of unbound glyoxal can be reduced, the solvation delay is reduced due to the addition of sodium tetraborate and the associated increase in pH. There was also no clear mention of storage stability. Furthermore, the glyoxal-reducing effect is low, and the additional additives used are not without problems from a toxicological perspective.
[0012] WO 2012 / 122153 A1 comprises a dry blend consisting of a standard commercial cellulose ether reversibly crosslinked with glyoxal and a partially neutralized powdered solid water-soluble polycarboxylic acid. The acid is preferably partially neutralized poly(meth)acrylic acid, polymaleic acid, citric acid, adipic acid, oxalic acid, malonic acid, or glutaric acid. When the crosslinked cellulose ether is stirred in water, the acid lowers the pH, causing the hemiacetal bonds to break more slowly and preventing the formation of lumps. WO 2014 / 175903 relates to a method for dispersing an anhydrous cellulose ether formulation into an aqueous solution without lumps. The cellulose ether formulation comprises a reversibly crosslinked cellulose ether and a solid water-soluble acid, preferably citric acid, tartaric acid, oxalic acid, malonic acid, or poly(meth)acrylic acid. The above formulation is a dry blend composed of standard commercial crosslinked cellulose ether and acid.
[0013] The present invention aims to reduce the content of bound and unbound glyoxal in cellulose ethers without altering the properties of the cellulose ethers, particularly solvation retardation and viscosity. By doing so, the present invention aims to significantly minimize health risks and avoid mandatory labeling.
[0014] Unexpectedly, it was discovered that the efficiency of glyoxal crosslinking can be increased by adding an acidic organic catalyst to a glyoxal solution buffered with an alkali metal salt or alkaline earth metal salt of phosphoric acid—specifically, by adding an organic acid that is aromatic or has a basicity of 1 or higher—thereby significantly reducing the amount of glyoxal used. The solvation delay for the cellulose ether with reduced glyoxal content prepared in the present invention is comparable to the solvation delay for the cellulose ether prepared according to the prior art. Surprisingly, the expected decrease in viscosity through a decrease in the pH of the product did not occur.
[0015] Accordingly, the subject of the present invention is a method for producing a cellulose derivative having delayed water solubility by reversibly crosslinking with glyoxal, wherein
[0016] a) a step of providing a water-moist cellulose derivative,
[0017] b) providing an aqueous solution comprising glyoxal and one or more alkaline earth metal salts and / or alkali metal salts of phosphoric acid as a buffer substance,
[0018] c) a step of mixing the aqueous solution from step b) and the cellulose derivative from step a) at a temperature of 20 to 70°C to achieve reversible crosslinking of the cellulose derivative,
[0019] d) a step of drying the reversibly crosslinked cellulose derivative and
[0020] e) including the step of grinding the cellulose derivative,
[0021] The above steps d) and e) can be combined to form a grinding-drying operation, and
[0022] The aqueous solution according to step b) comprises an organic acid having a basicity of 1 or higher, and
[0023] The amount of the organic acid having a basicity of 1 or higher per mole of anhydrous glucose units of the cellulose derivative is 0.002 to 0.015 mol, and the amount of glyoxal per mole of anhydrous glucose units of the cellulose derivative is 0.010 to 0.030 mol, and
[0024] The method includes a molar ratio of a monobasic organic acid to glyoxal in the range of 1:1 to 1:6, preferably 1:1 to 1:4, a molar ratio of a dibasic organic acid to glyoxal in the range of 1:1 to 1:10, preferably 1:2 to 1:6, and a molar ratio of a tribasic organic acid to glyoxal in the range of 1:2 to 1:12, preferably 1:3 to 1:8.
[0025] A further subject of the present invention is a reversibly crosslinked cellulose derivative prepared by the above method, namely, a cellulose derivative reversibly crosslinked with glyoxal, wherein
[0026] The cellulose derivative is reversibly crosslinked with glyoxal, characterized in that, per mole of anhydrous glucose units of the cellulose derivative, the fraction of an organic acid with a basicity of 1 or higher is 0.002 to 0.015 mol, per mole of anhydrous glucose units of the cellulose derivative, the amount of glyoxal is 0.010 to 0.050 mol, and the molar ratio of the organic acid with a basicity of 1 or higher to glyoxal is in the range of 1:2 to 1:12. The reversibly crosslinked cellulose derivative of the present invention preferably contains less than 1,000 ppm of free glyoxal.
[0027] Organic acids include monobasic, dibasic, tribasic, or polybasic organic acids. The organic acids are aliphatic, aromatic, and / or heterocyclic, preferably C1-C7 carboxylic acids having one to three carboxyl groups, which may also contain functional groups, e.g., hydroxyl groups and / or amino groups. Aromatic and heterocyclic acids may further include nitrogen, oxygen, or sulfur as heteroatoms. Aliphatic acids may likewise have at least one double bond. The acids used are more preferably acids used in the pharmaceutical and / or food sectors. pK a For monocarboxylic acids with a range of 2.5 or more and less than 5, these are acetic acid, lactic acid, and salicylic acid, and pK a1 The range of is 2.5 to 5 and pK a2For di- or tricarboxylic acids with a g of 6 or less, this is preferably adipic acid, tartaric acid, or malic acid. Carboxylic acids that are solid under standard conditions are generally preferred. This is also easier to meter. Acetic acid is less preferred due to its strong odor and relatively high volatility. In each case, the amount of acid is 0.002 to 0.015 mol, more preferably 0.004 to 0.010 mol per mole of anhydrous glucose unit of cellulose ether.
[0028] Glyoxal is preferably used in the form of an aqueous solution of about 40 wt%. In each case, the amount of glyoxal is 0.010 to 0.050 mol, more preferably 0.015 to 0.025 mol per mol of anhydrous glucose unit of cellulose ether.
[0029] The buffer used is an alkali metal salt or alkaline earth metal salt of phosphoric acid, more preferably an alkali metal salt of phosphoric acid, very preferably sodium dihydrogen phosphate monohydrate and disodium hydrogen phosphate. In each case, the amounts of sodium dihydrogen phosphate and disodium hydrogen phosphate are preferably 0.003 to 0.015 mol, more preferably 0.005 to 0.009 mol per mole of anhydrous glucose units of cellulose ether.
[0030] The cellulose derivative used is preferably a moisture-wet cellulose ether obtained after hot water washing, having a moisture content of 30 to 70 wt%. The moisture-wet cellulose ether is kneaded with a solution, preferably an aqueous solution, consisting of the acid used, a phosphate salt, and glyoxal, and subsequently dried and ground or processed by a grinding-drying operation. The solution is used to set the pH and to increase the efficiency of glyoxal crosslinking. As a result, the amount of glyoxal used can be significantly reduced, while the same solvation retardation as in the case of cellulose ethers prepared according to the prior art is obtained. The cellulose derivative is a nonionic cellulose ether, preferably methylhydroxyethylcellulose, methylhydroxypropylcellulose, methylcellulose, or a mixture thereof. Specific details for implementing the invention
[0031] Examples
[0032] In the following tables and examples, percentage fractions are reported as weight percentages.
[0033] To verify the storage stability of the cellulose ether prepared in the present invention, the aging of the sample was simulated by an accelerated test according to ASTM D6819. For the test, the air-dried cellulose ether is transferred to a temperature-stable glass container with a leak-proof sealing cap. The mass ratio of the sample being aged to the volume of the glass container must always be the same (2.76 g of completely dried (bone-dried) cellulose ether per 100 ml). Subsequently, the sample is adjusted to a constant moisture content of 10 wt% and stored at 100°C for 6 hours.
[0034] The reported solvation delay was measured using a Brabender viscometer (single speed 75 rpm, load cell 250 cmg, measuring sensor with measuring port and pin) in an aqueous solution (mains water at 20°C). Solvation time (ST) is the time (min) between the addition of the product and the attainment of a viscosity of 100 Brabender units (BU) = 65 mPa·s. Solvation end time (SET) is the time (min) at which there is no further increase in viscosity. For individual viscosity stages, the concentration of the measuring solution, the initial mass of the material, and the amount of dissolved water are evident from the table below.
[0035]
[0036] The pH of the cellulose ether was measured from a 1 wt% aqueous solution of completely dried cellulose ether using a pH meter equipped with a combined pH electrode.
[0037] The viscosity of the cellulose ether was measured using a Brookfield rotational viscometer (model DVI) from a 1.9 wt% aqueous solution of completely dried cellulose ether at 20°C, using spindle 5 for the 16,000 mPa·s viscosity stage and spindle 4 for the 5,000 mPa·s viscosity stage at a rotational speed of 20 rpm. The hardness of the water used to prepare the sample solution was 20° dH (German hardness).
[0038] Quantitative measurement of methoxy(-OCH3), hydroxyethyl(-OC2H4), and hydroxypropyl(-OC3H6) content and calculation of DS (mean degree of substitution) and MS (molar degree of substitution) are based on the reaction with hydroiodic acid and the literature [ Z. Anal. Chem. 286
[1997] 161-190] The alkyl iodide produced was confirmed by subsequent GC analysis according to the Zeisel method, which is familiar to those skilled in the art.
[0039] The total glyoxal content was determined by colorimetric analysis through the reaction of dissolved glyoxal with 3-methyl-2-benzothiazolinone hydrazone hydrochloride (MBTH) in an acidic medium. For this purpose, 0.1 g of air-dried cellulose ether was dissolved in 100 g of distilled water for 24 hours. The dissolution procedure must not be accelerated by alkalization. 2 ml of the cellulose ether solution was pipetteed into the reaction vessel, and 5 ml of a reagent solution (composed of 0.2 g MBTH, 10 g of deionized water, and 40 g of glacial acetic acid) was added to it via pipette. The reaction vessel was sealed, the reaction mixture was briefly mixed by shaking, and left in the dark for 2 hours. After the 2-hour reaction time, the absorbance of the sample and blank sample was measured at 405 nm in a 1 cm cuvette using a Dr. Lange CADAS 100 photometer. The absorbance of the sample must be between 0.100 and 2.000. If the absorbance is less than 0.100, the result is reported as <400 ppm glyoxal. If the absorbance is greater than 2.000, the CE solution was diluted by serial dilution prior to the reaction.
[0040] calculate
[0041]
[0042] E P = Absorbance of the sample
[0043] E0 = Absorbance of blank sample
[0044] F = Dilution factor
[0045] E = initial mass (g)
[0046] 4.207 = Slope of the correction line
[0047] To measure free, i.e., unbound glyoxal, 0.2 g of air-dried cellulose ether was mixed with 10 ml of tetrahydrofuran. The THF-cellulose ether suspension was shaken with a shaker for 4 hours and then filtered into a test tube through a fluted filter. 2 ml of the extract was mixed with 5 ml of MBTH reaction solution (composed of 0.2 g MBTH, 10 g deionized water, and 40 g glacial acetic acid), left in the dark for 2 hours, and then colorimetrically measured at 405 nm (Dr. Lange's CADAS 100 photometer) (see procedure for measuring total glyoxal content).
[0048] Example 1
[0049] A moisture-wet methylhydroxyethylcellulose MHEC (200 g of dry material) with an average degree of substitution DS (methyl) (DS represents the average number of methyl groups per anhydrous glucose unit) of 1.55, a molar degree of substitution MS (hydroxyethyl) (MS represents the average number of hydroxyethyl groups per anhydrous glucose unit) of 0.22, and a viscosity of 16,000 mPa·s was placed in an Erweka Apparatebau GmbH LK5 laboratory kneader and mixed with an aqueous solution of water, citric acid, sodium hydroxide, and glyoxal. The target moisture content for the MHEC was set using ice to 73%. Once all components were added, the entire mixture was kneaded for 30 minutes. Subsequently, the wet product was pre-dried by hand in a fluidized bed dryer and then dry-grinded using an Alpine mill (Model D 100 UPZ) with a 180 µm sieve. The target final moisture content was less than 5%.
[0050]
[0051] Example 2
[0052] A moisture-wet MHEC (200 g dry weight) with an average degree of substitution DS (methyl) of 1.55, a molar degree of substitution MS (hydroxyethyl) of 0.22, and a viscosity of 16,000 mPa·s was placed in an LK5 laboratory kneader of Erweka Apparatebau GmbH and mixed with water, an aqueous solution of sodium dihydrogen phosphate·H2O, disodium hydrogen phosphate, and glyoxal. A target moisture content of 73% for the MHEC was set using ice. Once all components were added, the entire mixture was kneaded for 30 minutes. Subsequently, the wet product was pre-dried by hand in a fluidized bed dryer and dried using an Alpine mill (Model D 100 UPZ) with a 180 µm sieve. A final moisture content of less than 5% was achieved.
[0053]
[0054] It is evident that when using phosphate buffer (Examples 2-1 and 2-2), the pH of the cellulose ether increases compared to the cellulose ether prepared according to the prior art (Example 1), while the viscosity before aging remains the same. After aging the samples, the viscosity decreases to a similar level. In glyoxal crosslinking, the solvation retardation ST was lower based on the elevated pH of the cellulose ether using phosphate buffer. However, in the case of the cellulose ether using phosphate buffer (Example 2-1), the post-crosslinking rate captured through aging simulation increased.
[0055] Example 3
[0056] A moisture-wet MHEC (200 g dry weight) with an average degree of substitution DS (methyl) of 1.55, a molar degree of substitution MS (hydroxyethyl) of 0.22, and a viscosity of 16,000 mPa·s was placed in an LK5 laboratory kneader of Erweka Apparatebau GmbH and mixed with an aqueous solution of sodium dihydrogen phosphate·H2O, disodium hydrogen phosphate, citric acid, water, and glyoxal. A target moisture content of 73% for the MHEC was set using ice. Once all components were added, the entire mixture was kneaded for 30 minutes. Subsequently, the wet product was pre-dried by hand in a fluidized bed dryer and dried using an Alpine mill (Model D 100 UPZ) with a 180 µm sieve. A final moisture content of less than 5% was achieved.
[0057]
[0058] The addition of citric acid as a catalyst for glyoxal crosslinking in the phosphate buffer significantly increased the ST. However, the viscosity after aging decreased much more significantly than in MHEC without the addition of acid to the glyoxal solution, resulting in a product that was not storage-stable. The post-aging crosslinking rate decreased as a result of the addition of citric acid. Glyoxal crosslinking was more efficient, and this was catalyzed by acid.
[0059] Example 4
[0060] A moisture-wet MHEC (200 g dry weight) with an average degree of substitution DS (methyl) of 1.55, a molar degree of substitution MS (hydroxyethyl) of 0.22, and a viscosity of 16,000 mPa·s was placed in an LK5 laboratory kneader of Erweka Apparatebau GmbH and mixed with an aqueous solution of sodium dihydrogen phosphate·H2O, disodium hydrogen phosphate, lactic acid, water, and glyoxal. A target moisture content of 73% for the MHEC was set using ice. Once all components were added, the entire mixture was kneaded for 30 minutes. Subsequently, the wet product was pre-dried by hand in a fluidized bed dryer and dried using an Alpine mill (Model D 100 UPZ) with a 180 µm sieve. In this way, a final moisture content of less than 5% was achieved.
[0061]
[0062] The addition of lactic acid to the phosphate buffer as a catalyst for glyoxal crosslinking significantly increased the ST. Consequently, the amount of glyoxal used could be reduced by half. As a result, the total glyoxal content and free glyoxal content in the MHEC were also significantly reduced. The product is no longer subject to labeling requirements. The loss of viscosity after aging was minimal and similar to that observed when using pure phosphate buffer. As a result of adding lactic acid, the post-crosslinking rate after aging was lower than that of the MHEC without the addition of acid to the phosphate buffer.
[0063] Example 5
[0064] A moisture-wet MHEC (200 g dry weight) with an average degree of substitution DS (methyl) of 1.55, a molar degree of substitution MS (hydroxyethyl) of 0.22, and a viscosity of 16,000 mPa·s was placed in an LK5 laboratory kneader of Erweka Apparatebau GmbH and mixed with an aqueous solution of sodium dihydrogen phosphate·H2O, disodium hydrogen phosphate, acetic acid, water, and glyoxal. A target moisture content of 73% for the MHEC was set using ice. Once all components were added, the entire mixture was kneaded for 30 minutes. Subsequently, the wet product was pre-dried by hand in a fluidized bed dryer and dried using an Alpine mill (Model D 100 UPZ) with a 180 µm sieve. A final moisture content of less than 5% was achieved.
[0065]
[0066] As a result of adding acetic acid to the phosphate buffer as a catalyst for glyoxal crosslinking, the ST could be maintained even though the amount of glyoxal used was reduced by half. Consequently, the total glyoxal value and the unbound / free glyoxal value in the MHEC also decreased significantly. The product is no longer subject to labeling requirements. The loss of viscosity after aging was minimal and similar to that when using pure phosphate buffer. As a result of adding acetic acid, the post-crosslinking rate after aging was lower than in the case of MHEC without acid added to the phosphate buffer.
[0067] Example 6
[0068] A moisture-wet MHEC (200 g dry weight) with an average degree of substitution DS (methyl) of 1.55, a molar degree of substitution MS (hydroxyethyl) of 0.22, and a viscosity of 16,000 mPa·s was placed in an LK5 laboratory kneader of Erweka Apparatebau GmbH and mixed with an aqueous solution of sodium dihydrogen phosphate·H2O, disodium hydrogen phosphate, adipic acid, water, and glyoxal. A target moisture content of 73% for the MHEC was set using ice. Once all components were added, the entire mixture was kneaded for 30 minutes. Subsequently, the wet product was pre-dried by hand in a fluidized bed dryer and dried using an Alpine mill (Model D 100 UPZ) with a 180 µm sieve. A final moisture content of less than 5% was achieved.
[0069]
[0070] As a result of adding adipic acid to the phosphate buffer as a catalyst for glyoxal crosslinking, the ST increased significantly. Consequently, the amount of glyoxal used could be reduced by two-thirds. Therefore, there was a significant reduction in total glyoxal and free glyoxal in the MHEC. The loss of viscosity after aging was low and similar to that when using pure phosphate buffer. The post-aging crosslinking rate was negligible or could no longer be determined due to the addition of adipic acid. Therefore, the product is not subject to labeling requirements. The ST and storage stability were identical to those of cellulose ethers prepared according to the prior art.
[0071] Example 7
[0072] A moisture-wetted MHEC (200 g dry weight) with an average degree of substitution DS (methyl) of 1.62, a molar degree of substitution MS (hydroxyethyl) of 0.21, and a viscosity of 5,000 mPa·s was placed in an LK5 laboratory mixer of Erweka Apparatebau GmbH. There, the moisture-wetted cellulose ether was mixed with an aqueous solution of glyoxal, water, citric acid, and sodium hydroxide (Batch No. 7-1, comparative) or with an aqueous solution of sodium dihydrogen phosphate·H2O, disodium hydrogen phosphate, water, and glyoxal (Batch No. 7-2, comparative) and with the acids indicated in the table (Batch Nos. 7-3 to 7-6). The target moisture content for the MHEC was set using ice. Once all components were added, the entire mixture was kneaded for 30 minutes. Subsequently, the wet product was pre-dried by hand in a fluidized bed dryer and dried using an Alpine mill (Model D 100 UPZ) with a 180 µm sieve. In this way, a final moisture content of less than 5% was achieved.
[0073]
[0074] From the table above, it is clear that positive effects can be obtained with the novel crosslinking agent / buffer solution even for different initial viscosities of MHEC.
Claims
Claim 1 A method for preparing a cellulose derivative having delayed water solubility by reversibly crosslinking with glyoxal, wherein the cellulose derivative is a nonionic cellulose ether, and the method comprises: a) providing a water-moist cellulose derivative; b) providing an aqueous solution comprising glyoxal and one or more alkaline earth metal salts and / or alkali metal salts of phosphoric acid as a buffer substance; c) mixing the aqueous solution from step b) and the cellulose derivative from step a) at a temperature of 20 to 70°C to achieve reversible crosslinking of the cellulose derivative; d) drying the reversibly crosslinked cellulose derivative; and e) grinding the cellulose derivative, wherein steps d) and e) may be combined to form a grinding-drying operation, and the aqueous solution according to step b) comprises an organic acid having a basicity of 1 or higher, and the molar amount of anhydrous glucose units of the cellulose derivative, monobasic, A method for manufacturing, characterized in that the amount of a dibasic, tribasic, or polybasic organic acid is 0.002 to 0.015 mol, the amount of glyoxal is 0.010 to 0.050 mol per molar of anhydrous glucose unit of the cellulose derivative, the molar ratio of a monobasic organic acid to glyoxal is in the range of 1:1 to 1:6, the molar ratio of a dibasic organic acid to glyoxal is in the range of 1:1 to 1:10, and the molar ratio of a tribasic organic acid to glyoxal is in the range of 1:2 to 1:
12. Claim 2 A method of manufacturing according to claim 1, characterized in that the cellulose derivative is methylhydroxyethylcellulose, methylhydroxypropylcellulose, methylcellulose, or a mixture thereof. Claim 3 A manufacturing method according to claim 1, characterized in that the cellulose ether takes the form of a filter cake having a dry matter content of 30 to 70% after hot water washing. Claim 4 A method of manufacturing according to claim 3, characterized in that the filter cake is added to a crosslinking agent solution consisting of glyoxal, a salt of phosphoric acid, an organic acid, and optionally water, and kneaded while continuously mixing, and subsequently the filter cake is dried and ground, or processed by a grinding-drying operation. Claim 5 A method of manufacturing according to claim 4, characterized in that glyoxal is mixed with the cellulose ether in a fraction of 0.035 mol or less per mole of anhydrous glucose units of the cellulose ether; or glyoxal is mixed with the cellulose ether in a fraction of 0.01 to 0.03 mol per mole of anhydrous glucose units of the cellulose ether. Claim 6 A method of preparation characterized in that, in any one of claims 1 to 5, the organic acid having a basicity of 1 or higher is mixed with the cellulose ether in a fraction of 0.004 to 0.010 mol per mol of anhydrous glucose unit of the cellulose ether. Claim 7 A method for manufacturing according to any one of claims 1 to 5, wherein the organic acid used, having a basicity of 1 or higher, is an aliphatic, aromatic and / or heterocyclic carboxylic acid, or an aliphatic saturated or unsaturated carboxylic acid having 1 to 7 carbon atoms and 1 to 3 carboxyl group(s), and the organic acid may contain a functional group, or the organic acid may contain a hydroxyl group and / or an amino group. Claim 8 A method of manufacturing according to claim 7, characterized in that the organic acid used, having a basicity of 1 or higher, is acetic acid, lactic acid, salicylic acid, adipic acid, citric acid, tartaric acid, and / or malic acid. Claim 9 A method of preparation according to claim 1, wherein the alkali metal salt of the phosphoric acid is sodium dihydrogen phosphate and disodium hydrogen phosphate, and the sodium dihydrogen phosphate and disodium hydrogen phosphate are each mixed into the cellulose ether in an amount of 0.003 to 0.015 mol per mole of anhydrous glucose unit of the cellulose ether, or mixed into the cellulose ether in an amount of 0.005 to 0.009 mol per mole of anhydrous glucose unit of the cellulose ether. Claim 10 A method of manufacturing according to claim 1, characterized in that the pH of the buffer / crosslinking agent solution is 3 to 8, or 4 to 6.
5. Claim 11 A cellulose derivative reversibly crosslinked with glyoxal, wherein the cellulose derivative is a nonionic cellulose ether, and the cellulose derivative reversibly crosslinked with glyoxal comprises, per mole of anhydrous glucose units of the cellulose derivative, an organic acid having a basicity of 1 or higher in a fraction of 0.002 to 0.015 mol, glyoxal in a fraction of 0.010 to 0.050 mol, glyoxal as a buffer substance, and one or more alkaline earth metal salts and / or alkali metal salts of phosphoric acid, wherein the molar ratio of the organic acid having a basicity of 1 or higher to the glyoxal is 1:1 to 1:
12. Claim 12 A cellulose derivative reversibly crosslinked with glyoxal according to claim 11, characterized in that the cellulose derivative reversibly crosslinked with glyoxal is methylhydroxyethylcellulose, methylhydroxypropylcellulose, methylcellulose, or a mixture thereof. Claim 13 A cellulose derivative reversibly crosslinked with glyoxal, characterized in that, in claim 11 or 12, the organic acid having a basicity of 1 or higher is acetic acid, lactic acid, salicylic acid, adipic acid, citric acid, tartaric acid, and / or malic acid. Claim 14 A cellulose derivative reversibly crosslinked with glyoxal according to claim 11 or 12, wherein the alkali metal salt of the phosphoric acid is sodium dihydrogen phosphate and disodium hydrogen phosphate, and the amount of sodium dihydrogen phosphate and disodium hydrogen phosphate contained in the cellulose derivative reversibly crosslinked with glyoxal is, in each case, 0.002 to 0.015 mol per mole of anhydrous glucose unit of the cellulose ether, or 0.005 to 0.009 mol per mole of anhydrous glucose unit of the cellulose ether. Claim 15 A cellulose derivative reversibly crosslinked with glyoxal according to claim 11 or 12, characterized in that the cellulose derivative reversibly crosslinked with glyoxal contains less than 1,000 ppm of free glyoxal.
Citation Information
Patent Citations
Water-Dispersible Polysaccharide Derivatives ofReduced Glyoxal Content, and a Process for Decreasingthe Glyoxal Content in Glyoxal-CrosslinkedPolysaccharide Derivatives
KR1020040076802A
Method for Preparing Acetylated Cellulose Ether Having Improved Anti-Fouling and Acetylated Cellulose Ether Prepared by the Method
KR1020140074049A
Cellulose ethers with temporary cross-links, a process to make them, and their use
KR1020180056734A
